2005
DOI: 10.1210/en.2004-1360
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Stimulates Mammary Gland Ductal Morphogenesis by Synergizing with and Enhancing Insulin-Like Growth Factor-I Action

Abstract: Progestins have been implicated in breast cancer development, yet a role for progesterone (Pg) in ductal morphogenesis (DM) has not been established. To determine whether Pg could cause DM, we compared relative effects of Pg, estradiol (E2) and IGF-I on anatomical and molecular biological parameters of IGF-I-related DM in oophorectomized female IGF-I(-/-) mice. Pg had little independent effect on mammary development, but together with IGF-I, in the absence of E2, Pg stimulated an extensive network of branching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 44 publications
5
47
0
1
Order By: Relevance
“…It is possible that mifepristone may reduce cancer development by upregulation of inhibitory factors such as TGF-b1 and/or downregulation of stimulatory pathways including IGF. Progesterone and IGF increase ductal elongation in the mammary gland (Ruan et al, 2005) and progesterone and the PR-B isoform has been shown to increase insulin receptor substrate-2 expression (Vassen et al, 1999;Cui et al, 2003). One can speculate that the enhanced ductal elongation observed in the Brca1-deficient mice was secondary to increased PR and IGF signaling in the pubertal mice.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that mifepristone may reduce cancer development by upregulation of inhibitory factors such as TGF-b1 and/or downregulation of stimulatory pathways including IGF. Progesterone and IGF increase ductal elongation in the mammary gland (Ruan et al, 2005) and progesterone and the PR-B isoform has been shown to increase insulin receptor substrate-2 expression (Vassen et al, 1999;Cui et al, 2003). One can speculate that the enhanced ductal elongation observed in the Brca1-deficient mice was secondary to increased PR and IGF signaling in the pubertal mice.…”
Section: Discussionmentioning
confidence: 97%
“…A role for IGF-1 in the branching we have described cannot be eliminated. Indeed, Ruan et al (2005) have shown that in the absence of E, IGF-1 and P act synergistically to develop the branched ductal tree. During branching, IGF-1 and E (Zhang et al, 2002) act indirectly on the epithelium through the stroma while our data indicate that P acts directly on the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Negative controls for pYIRS-1 identification were incubated with primary antibody preabsorbed with 200-fold molar excess of the pYIRS-1 phospho-peptide. As previously published, antibody specificity for pYIRS-1 was also determined by Western blotting of MCF-7 cell proteins [9]. Omission of the primary antibody and replacement with non-immune IgG was used as a negative control for Ki67 staining.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…We reported that GH-stimulated IGF-I was essential for mammary development [5][6][7]. IGF-I, in fact, mediates the known effects of GH in mammary development [8], and is also required for E 2 and progesterone action (singly or together) [9]. Inhibition of IGF-I action by IGF-I binding protein (IGFBP)1 and IGFBP5 has also been shown to prevent mammary development [10,11].…”
Section: Introductionmentioning
confidence: 99%